Serum estradiol and progesterone in the mid-luteal phase predict clinical pregnancy outcome in IVF/ICSI cycles. (July 2013) - Sonntag, Barbara; Loebbecke, Kay C.; Nofer, Jerzy-Roch; Kiesel, Ludwig; Greb, Robert R.
Abstract In this prospective study, we tested the hypothesis if E2 and P serum levels significantly differ during the luteal phase following in vitro-fertilization/intracytoplasmic sperm injection (IVF/ICSI) therapy in conception (CC) versus non-conception (NC) cycles, and their potential in the prediction of pregnancy at the earliest point in time. Serum was sampled from the day of embryo transfer (ET) and throughout the luteal phase until ET + 14 from patients consecutively enrolling for IVF/ICSI therapy. The luteal phase was supported by vaginal P suppositories only, clinical pregnancies were detected by ultrasound and followed up until the 20th week. Overall pregnancy rate was 30.9% constituting the two study groups of CC (n = 22) and NC cycles (n = 49). Significantly, higher E2 (3326 ± 804 versus 1072 ± 233 pmol/l, p = 0.014) and P (244 ± 68 versus 73 ± 10 nmol/l, p = 0.023) were present in CC versus NC from as early as ET + 7. In the CC group, patients with ongoing pregnancies (CC-OG) as compared with miscarriages (CC-MC) had significantly higher E2 and P from ET + 7, predicting ongoing pregnancy in receiver operator characteristics analysis.